Anatomy of modern sedimentary volcanoes produced by gas‐charged groundwater liquefaction, Lake Powell, Hite, Utah: Implications for the recognition and interpretation of ancient sedimentary volcanoes - Michael C. Wizevich; Edward L. Simpson; Abigail Underwood; Laura Sherrod; Kelsey Livingston; Emily Bogner; Margariete Malenda (The Depositional Record)
Abstract Numerous sedimentary volcanoes, recently exposed on the Colorado River delta surface at Lake Powell near Hite, Utah, were generated by sediment slurries propelled by gas, mainly microbially generated methane (CH4). Two sedimentary volcanoes were excavated, one in 2016 and the other in 2019, in order to characterise the internal structures. Comparison of the internal structures of these features with those of previously documented seismic‐generated sedimentary volcanoes helps in differentiating the various modes of mobilised sediment generation. Sedimentary volcanoes are commonly employed as tools in palaeoseismic reconstruction, thus it is important to establish criteria to differentiate non‐seismic‐generated sedimentary volcanoes and accompanying sediment deformation from those features generated by earthquakes. Trenches through the volcanoes and immediate subsurface areas reveal a complex cone stratigraphy of centimetre‐scale graded sand‐silt laminations and clastic dikes that cross‐cut the cone and sub‐cone (delta) sediment. Some cone strata have ripple cross laminations, a scoured base and are disrupted by soft‐sediment deformation. In the 2016 volcano, the lowest 0.5 m of the dikes exposed in the trench are filled with organic‐rich mud, but these conduits are empty nearer to the surface as a result of sediment settling after eruption cessation. The 2019 sedimentary volcano differs from the other by: (1) more cross laminations in the cone, (2) collapse structures surrounding the crater, (3) a relatively simple plumbing system assisted by desiccation‐generated fissures and (4) a massive sediment infill of the vent. Both complex internal cone stratigraphy and the two distinct cross‐cutting dike‐conduit systems, unequivocally generated by recurrent gas and water discharge, add to the database of features for non‐seismic‐generated sedimentary volcanoes. This array of sedimentary structures from a non‐seismic‐generated sedimentary volcano demonstrates that certain features, including numerous internal laminations composing the cone and complex generations of dike systems are not unique to seismic‐generated sand volcanoes.